2019
DOI: 10.3390/cells8050419
|View full text |Cite
|
Sign up to set email alerts
|

Gait Training in Virtual Reality: Short-Term Effects of Different Virtual Manipulation Techniques in Parkinson’s Disease

Abstract: It is well documented that there is a strong relationship between gait asymmetry and the freezing of gait (FOG) in Parkinson’s Disease. The purpose of this pilot study was to find a “virtual reality (VR)- based” gait manipulation strategy to improve gait symmetry by equalizing step length. Fifteen male PD patients (mean age of 67.6 years) with FOG were assessed on a GAITRite® walkway. Natural gait was compared with walking conditions during “VR-based” gait modulation tasks that aimed at equalizing gait symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 52 publications
0
28
0
6
Order By: Relevance
“…In recent years with the increasing offers and decreasing price of immersive VR technology on the market, a few more studies have used immersive VR technology such as HTC vive and Oculus Rift for gait and balance training for people with PD [ 15 , 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years with the increasing offers and decreasing price of immersive VR technology on the market, a few more studies have used immersive VR technology such as HTC vive and Oculus Rift for gait and balance training for people with PD [ 15 , 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…[6][7][8] Recent experimental studies have reported the beneficial influence of virtual reality (VR) training strategies to enhance gait performance poststroke. 3,[9][10][11] These studies have reported enhancements in spatiotemporal gait parameters while suggesting an enhancement in gait stability, 12 hence inferred in this study as an enhancement in gait performance. Typically, VR can be defined as an application that, in very near real-time, allows a user to navigate through, and interact with, a virtual environment.…”
Section: Introductionmentioning
confidence: 49%
“…Recent experimental studies have reported the beneficial influence of virtual reality (VR) training strategies to enhance gait performance poststroke 3,9–11 . These studies have reported enhancements in spatiotemporal gait parameters while suggesting an enhancement in gait stability, 12 hence inferred in this study as an enhancement in gait performance.…”
Section: Introductionmentioning
confidence: 57%
“…Dopaminergic therapy has the best effect on gait velocity, stride length, and cadence, but this and other agents, including cholinergic (donepezil), glutamatergic, noradrenergic (methylphenidate, venlafaxine), and multi-mechanistic (amantadine) medications have variable and generally limited success. Because of the limited therapeutic options, several alternative modes of therapies have been tested in small studies to determine better treatment approaches for FOG, including the following: virtual reality [4,5], wearable assistive devices [6], robot-assisted gait training [7], and a single open-label study assessing the utility of Google Glass TM (GG) [8]. Though the first GG report utilizing external visual and auditory cues in 12 subjects with FOG demonstrated no significant change in FOG, a more stable gait pattern did emerge with auditory rather than visual cueing.…”
Section: Introductionmentioning
confidence: 99%